Penerapan Prinsip Good Corporate Governance Pada Koperasi Simpan Pinjam Di Kabupaten Cirebon - Ibrahim, Idris Abas (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2021)
The application of good corporate governance encourages the management of savings and loan cooperatives (KSP) to carry out their business activities by paying attention to the principles of cooperatives and the principles of prudence so that they become cooperatives that are transparent, accountable, and responsive. This study uses a social, legal approach while the data is obtained through field research and literature. Furthermore, the data were analyzed qualitatively. The problems are formulated: (1) how is the application of the principles of Good Corporate Governance (GCG) in savings and loan cooperatives in Cirebon ?; (2) what must be done so that the GCG principles can be fully implemented by KSP in Cirebon Regency? The results of the study concluded: 1) The application of the principles of Good Corporate Governance (GCG) in the Savings and Loans Cooperative (KSP) in Cirebon Regency is a necessity that must be carried out and enforced in Cirebon Regency. 2) Cooperatives in Cirebon have not fully implemented the principles of cooperatives, have more to do with the principles of GCG. 3) GCG principles must be part of cooperatives, especially in Cirebon Regency and generally for cooperatives in Indonesia. The following suggestions should be issued: 1) Regulations that regulate the obligation to apply cooperative principles and Good Corporate Governance should be published in the KSP so that the establishment of the KSP does not end with the closure of the KSP, which in the end is detrimental to its members. 2) KSP should be obliged to become a member of the Deposit Insurance Corporation so that if there is a KSP closure, it will not be detrimental to members who have deposited at the closed KSP. KSP members will trust KSP; 3) Guidance and supervision of cooperatives should be increased and intensified. Establish a National Accreditation Agency for Indonesian Cooperatives to spur improvement in managing cooperatives in Indonesia.